DIC Analyses and Parameter Calibration of a Strain Aging Sensitive Ductile Cast Iron - Valmalle, Malo; Widell, Kim; Ilola, Risto; Bossuyt, Sven (Comptes Rendus. Mécanique)
In the present work, the mechanical response of strain aging sensitive ductile cast iron was studied when subjected to uniaxial tension in temperatures ranging from 20°C up to 300°C. Digital Image Correlation (DIC) was used to measure the strain localization patterns due to dynamic strain aging. A constitutive law based on the Kubin–Estrin–McCormick model (KEMC) was used to model the behavior of the ductile cast iron in temperatures ranging from 20° up to 300°. The displacement fields were successfully measured and the strain localization patterns were observed. These measurements were employed to calibrate the parameters of the constitutive law. Numerical simulations are shown to be in agreement with experimental measurements at the macroscopic scale.